2001
DOI: 10.1007/s00296-001-0159-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum levels of soluble intercellular adhesion molecule-1 with disease activity in systemic lupus erythematosus

Abstract: Intercellular adhesion molecule-1 (ICAM-1) is a membrane-bound molecule primarily involved in cell-cell adhesive interactions of the immune system. It is a cytokine-induced glycoprotein involved in the recruitment of cells into tissues undergoing inflammatory responses. The levels of soluble ICAM-1 were measured in sera of patients with systemic lupus erythematosus (SLE) using sandwich enzyme-linked immunoassay. Serum levels (mean +/- SD) of soluble ICAM-1 (sICAM-1) were significantly higher in 24 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The cellular source of soluble ICAM-1 (sICAM-1) in samples of healthy blood donors seemed to be from mononuclear cell, because sICAM-1 was only detectable in cell culture supernatants of lymphoid cell lines and peripheral blood mononuclear cell cultures. Raised values of sICAM-1 have been reported in samples of patients with melanoma [6], systemic lupus erythematosus [10], metastatic cancer, and acute urolithiasis [6]. Our data confirm this condition in colorectal cancer patients for the first time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The cellular source of soluble ICAM-1 (sICAM-1) in samples of healthy blood donors seemed to be from mononuclear cell, because sICAM-1 was only detectable in cell culture supernatants of lymphoid cell lines and peripheral blood mononuclear cell cultures. Raised values of sICAM-1 have been reported in samples of patients with melanoma [6], systemic lupus erythematosus [10], metastatic cancer, and acute urolithiasis [6]. Our data confirm this condition in colorectal cancer patients for the first time.…”
Section: Discussionsupporting
confidence: 92%
“…Lipid-bound SA levels are correlated with the stage of the disease, degree of metastatic involvement, and recurrence of disease [11]. Serum TSA has been found to be increased in malignant melanoma [13], colorectal cancer [10], gastric cancer [16], head and neck cancer [14], laryngeal cancer [4], and breast cancer [15] and higher TSA levels were observed in cases of more developed malignancies [11]. In addition, these concentrations have been found to be higher in colorectal cancers [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with studies that show reduced CNS pathology on ICAM‐1 inhibition in patients and mouse models (Brey et al. 1997; Sari et al. 2002).…”
Section: What We Know About the Role Of Complement In Cns Diseasessupporting
confidence: 91%
“…Several other groups have attempted to correlate adhesion molecule levels with markers of disease activity. The results have been widely variable, although at least two studies demonstrated a correlation between VCAM-1 levels and disease activity [62,63,64]. Given the heterogeneity between studies and the disparate patterns of results, it is difficult to conclude that patients with SLE exhibit a distinct profile of adhesion molecule expression.…”
Section: Clinical Findings Of Major Chronic Inflammatory Diseases mentioning
confidence: 99%